2006
DOI: 10.1126/science.1128356
|View full text |Cite
|
Sign up to set email alerts
|

Frames, Biases, and Rational Decision-Making in the Human Brain

Abstract: Human choices are remarkably susceptible to the manner in which options are presented. This socalled "framing effect" represents a striking violation of standard economic accounts of human rationality, although its underlying neurobiology is not understood. We found that the framing effect was specifically associated with amygdala activity, suggesting a key role for an emotional system in mediating decision biases. Moreover, across individuals, orbital and medial prefrontal cortex activity predicted a reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

92
1,028
12
18

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,300 publications
(1,185 citation statements)
references
References 25 publications
(21 reference statements)
92
1,028
12
18
Order By: Relevance
“…Economic behavior and brain activation both respond to incentive magnitude differently depending on whether the incentive is a gain or a loss relative to a reference point (De Martino et al, 2006;Friedman and Savage, 1948;Kahneman and Tversky, 1979;Tom et al, 2007). Tom et al (2007) recently found NAcc responses to mixed gambles decreased more steeply with loss magnitude than they increased with gain magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Economic behavior and brain activation both respond to incentive magnitude differently depending on whether the incentive is a gain or a loss relative to a reference point (De Martino et al, 2006;Friedman and Savage, 1948;Kahneman and Tversky, 1979;Tom et al, 2007). Tom et al (2007) recently found NAcc responses to mixed gambles decreased more steeply with loss magnitude than they increased with gain magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Acredita-se que o córtex pré-frontal e o córtex orbitofrontal recebam aferências da amígdala, as quais representam o valor motivacional dos estímulos, integrando-os e promovendo uma avaliação do comportamento futuro que será adotado 25 .…”
Section: O Ego Segundo Freud E a Neurofisiologiaunclassified
“…O córtex cingulado anterior parece ser importante para a modulação das informações processadas pelo córtex pré-frontal 25 . Estudos de neuroimagem demonstram que processos executivos são mediados pelo córtex frontal, particularmente o córtex cingulado anterior e o córtex pré-frontal.…”
Section: O Ego Segundo Freud E a Neurofisiologiaunclassified
“…O CPFVM e o COF mantêm importante relação com a amígdala e ambos contribuem para a tomada de decisões, embora os mecanismos pelos quais isto ocorra sejam distintos. Acreditase que essas regiões corticais recebam aferências da 53 .…”
Section: Emoção E Razãounclassified
“…Embora a amígdala não estabeleça conexão direta com o córtex lateral pré-frontal, ela se comunica com o córtex cingulado anterior e o córtex orbital, os quais estão envolvidos nos circuitos da memória, tornando possível a justificativa de alguns autores de que a amígdala participa na modulação da memória e na integração de informações emocionais e cognitivas, possivelmente atribuindo-lhes carga emocional, possibilitando a transformação de experiências subjetivas em experiências emocionais 24,53 . Lesões no córtex pré-frontal medial rostral levam à expressão inapropriada das emoções nos comportamentos sociais e ao prejuízo na tomada de decisões pessoalmente vantajosas 28 .…”
Section: Emoção E Razãounclassified